2021
DOI: 10.3390/su131810430
|View full text |Cite
|
Sign up to set email alerts
|

Demolition-Based Urban Regeneration from a Post-Socialist Perspective: Case Study of a Neighborhood in Novi Sad, Serbia

Abstract: Although a growing body of literature examines the post-socialist European context of urban regeneration, studies on the demolition-based approaches are relatively scarce. Moreover, the regeneration policies of cities in non-EU Balkan countries with a distinctive transitional path remain largely unexplored. The paper contributes to filling these voids by investigating a specific demolition-based urban regeneration strategy named permanent reconstruction, which has been launched in Novi Sad, Serbia’s second lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…It should be appreciated that neighborhoods were designed for a maximum of 170 cars per 1000 inhabitants, whereas the current level of motorization is around 500 cars per 1000 inhabitants. This problem can always be found in the literature and in examples of revitalization [82,83]. Residents park their cars wherever possible-on the shoulders of the highway, on pavements, on lawns, etc.…”
Section: žIrmūnai Triangle Before Revitalizationmentioning
confidence: 99%
“…It should be appreciated that neighborhoods were designed for a maximum of 170 cars per 1000 inhabitants, whereas the current level of motorization is around 500 cars per 1000 inhabitants. This problem can always be found in the literature and in examples of revitalization [82,83]. Residents park their cars wherever possible-on the shoulders of the highway, on pavements, on lawns, etc.…”
Section: žIrmūnai Triangle Before Revitalizationmentioning
confidence: 99%
“…The number of complaints made has revealed that the DRP was developed without public involvement, i.e., in a rather non-transparent manner. Second, the rejection of proposals without convincing arguments implied that the plan was adoption-ready, as well as that the local officials did not perceive the public as an equal partner "but rather an obstacle to their agenda" [105] (p. 23). This confirmed what has already evolved into a post-socialist practice-participation in the planning process was only simulated through public presentations, representing a mere formality, while all key decisions have already been made elsewhere.…”
Section: (Lacking) Citizen Participation In the Planning Processmentioning
confidence: 99%